The Impact of Japan's Cultural Diplomacy Towards Indonesia: The Case Study of Asia Kakehashi Program - Putri, Paola Martha Adithya; Baskoro, Riski M (AEGIS : Journal of International Relations, 2024)
Given the richness of its culture, Japan then utilizes a cultural diplomacy strategy which is implemented to other countries, one of which is the Asia Kakehashi Project. The Asia Kakehashi Project is a student exchange scholarship program, designated specifically for countries in Asia, including Indonesia, in the period 2018 to 2022. To this research, the researcher aims to examine the implementation of the Asia Kakehashi Project as a strategy of Japanese cultural diplomacy towards Indonesia and uncovered impact of the program towards alumni of Asia Kakehashi project. This research uses qualitative methods, specifically ethnography then analyzed using the theory of soft power and cultural diplomacy. As for this research found that the Asia Kakehashi Project focuses on cultural learning in three main environments, namely Host Family/Dorm, School, and also Social Community. The Asia Kakehashi Project is one of Japan's cultural diplomacy strategies towards Indonesia that has successfully achieved its goals, namely the emergence of mutual understanding between Indonesia and Japan.